The regional distribution of public employment: Theory and evidence - Sebastian Kessing; Chiara Strozzi (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2016)
We analyze the optimal regional pattern of public employment in an information-constrained second-best redistribution policy showing that regionally differentiated public employment can serve as an expenditure side tagging device, bypassing or relaxing the equity-effciency trade-off. The optimal pattern exhibits higher levels of public employment in low productivity regions and is more pronounced the higher is the degree of regional inequality within the country. Empirically, using a panel of European regions from 1995-2007, we find evidence that public employment is systematically higher in low productivity regions. The latter effect is stronger in countries with higher levels of regional inequality.
Keywords: H11; J45; R12; 330; public employment; redistribution; regional inequality; European regions